Gas-solid interaction of H-2-Ce0.95Zr0.05O2: new insights into surface participation in heterogeneous catalysis - Jain, Ruchi; Dubey, Anjani; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Catalysis Science & Technology, 2016)
A direct interaction between a reduction medium (H-2) and a Ce0.95Zr0.05O2 (CZ) solid surface was explored through ambient pressure photoelectron spectroscopy (APPES), with conventional X-ray and He-I photon sources, in H-2 atmosphere up to 0.1 mbar pressure and 773 K. A porous CZ thin film was prepared by a combination of sol-gel and spin-coating methods, and was employed to understand the redox nature of ceria under reduction conditions. The maximum of 45% Ce3+ along with the corresponding oxygen vacancy was observed due to reduction. An unprecedented decrease in the valence band (VB) energy up to 1.4 eV was observed on reduction along with a narrowing of VB. The highest occupied energy band derived from Ce 4f also shifts closer to E-F. H-2 molecular vibration observed in VB-APPES was employed as a probe to explore the surface potential changes along with the dynamic change in the nature of the surface under reduction conditions. The surface potential decreases by 0.27 eV up to 673 K, and then it reverts by 0.24 eV on further reduction at 773 K for different reasons. Further, an enhancement in the Ce 5d-O 2p interaction occurs at the expense of the Ce 4f-O 2p interaction under the above reduction conditions. Vacuum annealing and H-2 reduction after that show significantly more VB shift and enhanced reduction than H-2 reduction alone. Although Ce reduction occurs on high temperature vacuum annealing of CZ, a significantly lower amount of oxygen vacancies appears. This study shows the dynamic changes in the nature of the surface due to a gas (H-2)-solid (CZ) interaction and ensuing electronic structure changes that influence heterogeneous catalysis. It also underscores the necessity to study the catalytic materials under in situ conditions or closer to that.

Seeding of Au on CdSe/CdS nanoplates using Langmuir-Blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2016)
Oleyl amine capped CdSe/CdS nanoplates were synthesized by hot injection technique which formed a stable monolayer over both a water subphase and an aqueous HAuCl4 subphase using a Langmuir-Blodgett trough. Au islands were generated at the edge as well as on one specific surface of the flat nanoplates by exploiting the reducing capacity of oleyl amine to form Au nanoseeds from AuCl4- ions. The initial Au nanoseeds changed to a shell surrounding these nanoplates on prolonged exposure to the subphase containing the Au precursor. Monolayer of the hybrid structures was deposited onto suitable substrates for characterization by a number of different techniques and to study the photocatalytic activity. The same substrate with the monolayers could be re-used in several cycles of photocatalysis.

Three way catalytic converter reactions aspects at near ambient temperatures on modified pd-surfaces - Roy, Kanak; Jain, Ruchi; Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Comptes Rendus Chimie, 2016)
The dissolution of oxygen in palladium plays an important role in palladium catalysis. The present study shows that the surface modification (SM) due to the dissolution of atomic oxygen into the subsurfaces of palladium can be used as a control to tune its catalytic activity. CO oxidation and NO + H-2 + O-2 reaction was separately carried out on metallic Pd and on surface modified Pd using a molecular beam instrument and the results were compared. The metallic Pd does not show activity below 400 K for both reactions, whereas the SM-Pd shows activity at near-ambient temperatures. The electronic change due to SM was investigated using ambient pressure photoelectron spectroscopy, and the investigation clearly shows the effect of subsurface oxygen in the ambient temperature activity of palladium. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.

Facile synthesis of Al2O3-Pt nanocomposite and its catalytic activity - Das, Subhasis; Bordoloi, Ankur; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (Materials Research Express, 2017)
Pt nanoparticles were synthesized on gamma-alumina support in presence of oleic acid which was found to prevent clustering of Pt nanoparticles on the support. Various percentage of Pt loading on the alumina changed the catalytic activity for preferential oxidation of CO at relatively low temperature in H-2 rich stream. Pt nanoparticles when synthesized in absence of oleic acid, were all clustered and did not have any catalytic activity. The presence of oleic acid promoted stability preventing agglomeration of Pt nanoparticles. The catalyst thus prepared was characterized thoroughly and their catalytic activity was studied in details.

Facile synthesis of ZnO-Ag nanocomposite and its photocatalytic activity - Sardar, Debasmita; Maity, Jayeta; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (Materials Research Express, 2017)
The evolution of photoactive hybrid materials (e.g. noble metal-semiconductor) has resulted in heterogeneous photocatalysis. We report a facile route for the synthesis of ZnO-Ag nanocomposites with varying percentage of loading of the noble metal, expecting a great boost in the photocatalytic behavior of ZnO. The as prepared material was thoroughly characterized by UV-Vis, FTIR, TEM, FESEM, XRD, XPS analyses. The photocatalytic activities of the nanocomposites have been assessed from the ability to degrade methylene blue dye in aqueous solution. The results suggest that incorporation of Ag nanoparticles on the surface of ZnO particles can enhance catalytic activity in comparison to pure ZnO particles under visible light by minimizing the recombination of photogenerated electron-hole pairs.

Metallic cobalt to spinel Co3O4-electronic structure evolution by near-ambient pressure photoelectron spectroscopy - Reddy, Kasala Prabhakar; Jain, Ruchi; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2017)
In the present study, valence band (VB) and core level photoelectron spectroscopy was carried out to investigate the electronic structural changes from polycrystalline Co to spinel Co3O4, via CoO at near ambient pressures (NAP; similar to 0.1). O-2 Co and H-2-CoOx gas solid oxidative and reductive interactions, respectively, have been explored with UV photons (He I) or low kinetic energy electrons (<= 16 eV) under NAP conditions. Typical VB features of Co metal, CoOx Co3O4, and a mixed phase between any two adjacent features were observed and well corroborated with core level changes. Very significant and characteristic changes were observed with Co 3d features in the VB for each stage from Co oxidation to Co3O4 as well as Co3O4 reduction to CoOx Co(3O)4 and CoO can be reversibly obtained by alternating the conditions between 0.1 mbar of H-2 at 650 K and 0.1 mbar of O 2 at 400 K, respectively. A meaningful correlation is observed between the changes in work function with cation oxidation state; small changes in the stoichiometry can strongly influence the shift in Fermi level and changes in work function under NAP conditions. Reversible work function changes are observed at a constant BE (similar to 5 ev) between oxidation and reduction conditions. While the O 2 p derived feature for CoOx was observed at throughout the redox conditions, the Co 3d band and molecular oxygen or hydrogen vibration feature shifts significantly underscoring the physicochemical changes, such as charge transfer energy and hence changes in satellite intensity. The peak close to E-F originated from the 3d(6)L final state of the octahedral Co3+ 3d band of Co3O4.

Water mediated deactivation of Co3O4 naonrods catalyst for CO oxidation and resumption of activity at and above 373 K: electronic structural aspects by NAPPES - Jain, Ruchi; Reddy, Kasala Prabhakar; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2017)
The catalytic activity of the Co3O4 nanorods (NRs) for the CO oxidation reaction and the effect of water on the catalytic reaction have been explored with near-ambient pressure photoelectron spectroscopy (NAPPES) and mass spectral analysis. Comparative NAPPES studies have been employed to understand the elucidation of the catalytic reaction pathway and the evolution of various surface species. The results confirm the suppression of the CO oxidation activity on the Co3O4 NRs in the presence of water vapor. Various type of surface species, such as CO(ads), hydroxyl, carbonate, formate, are found to be present on the catalyst surface depending on the reaction conditions. Vibrational features of CO, O-2, and CO, were observed and shift in binding energy of these features under the reaction conditions directly suggests a change in work function of the catalyst surface. Under dry conditions, CO couples with labile 0 atoms to form CO2; however, under wet conditions, CO predominantly interacts with surface OH groups resulting in the formation of carbonate and formate intermediates. In situ studies of oxidation of CO on Co3O4 shows that CO oxidation depends not only on surface Co3+ concentration but also influenced by Co-3/Co' ratio on the catalyst surface. The carbonate was found to be a reaction inhibitor at room temperature; however, it acts as an active intermediate at 375 K and above. Above the boiling point of water, Co3O4 NR surfaces begin to show the oxidation activity even in the presence of water vapor. The intrinsic role of intermediate species was used to derive a possible reaction mechanism under different reaction conditions.
Keywords: Ambinent-temprature; carbon monoxide; Gas Shift; H Activation; In-situ; Low-temprature oxidation; Molecular-beam; Performance enhancement; Ray Photoelectron-Spectroscopyu; Thin-films

Deposition of Au nanoparticles inside porous CeO2 nanocubes using Langmuir-Blodgett technique - Das, Subhasis; Bhattacharjee, Gourab; Satpati, Biswarup; Kumar, Mukesh; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2018)
Porous 3D CeO2 nanocubes were synthesized using hot injection technique. These nanocubes were able to form a stable monolayer over water and HAuCl4 subphase in Langmuir-Blodgett (LB) trough due to the presence of surface capped oleic acid and oleylamine. CeO2-Au nanocomposites were synthesized exploiting the ability of oleylamine to reduce AuCl4 ions to Au-0, via LB method. CeO2 nanocubes gave rise to excellent long-range assembly at air/water interface and gold nanoparticles were formed inside these porous nanocubes without disturbing this arrangement. The formation of a stable monolayer was evidenced from the surface pressure-area (P-A) isotherm. The development of Au nanoparticles was confirmed with great effort from a comprehensive study using UV-Vis spectroscopy, XRD, XPS, FTIR, TEM, STEM, EDX, tomography and chemical mapping.

Mapping valence band and interface electronic structure changes during the oxidation of Mo to MoO3 via MoO2 and MoO3 reduction to MoO2: A NAPPES study - Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Tuning the surface energetics, especially work function (phi) of the materials, is of a great deal of interest for a wide range of surface- and interface-based devices and applications. How the phi of a solid surface changes under the reaction conditions is of paramount interest to the chemists, particularly in the areas of surface dependent phenomena such as, catalysis and electrochemistry. In the present study, by using the valence band and core-level photoelectron spectroscopy, surface-electronic changes from Mo to MoO3 via MoO2 was studied under relevant near-ambient pressure (NAP) and high temperature conditions. A very significant change in phi from Mo to MoO3 was observed and it is well corroborated with the changes in gas-phase vibrational features of O-2 in both near-ambient pressure ultraviolet photoelectron spectra (NAPUPS) as well in NAP X-ray photoelectron spectroscopy. Reversible changes in the electronic structure is observed when MoO3 was reduced in H-2 to MoO2. On the basis of the extent of oxidation/reduction of MoOx NAPUPS has shown, one or two additional peaks in the band gap at 0.6 and 1.6 eV below the Fermi level. Mo5+ features are identified in the VB and in the Mo 3d core levels with distinct features. Mo5+ features are also stable and essential to bridge MoO2 and MoO3 layers, and their co-existence. In addition, characteristic changes in Mo 4d and O 2p features observed from Mo to MoO3 and well corelated to the band gap of MoO3. Oxidation and reduction propagate from the surface to bulk; indeed, this has significant implications in surface-dependent phenomena. The present study demonstrates (a) the uniqueness of NAPUPS in identifying the subtle to large changes in the electronic structure on solid surfaces under common oxidation and reduction (in general, under reaction) conditions, and (b) relevance of NAPUPS to all surface dependent phenomena, such as catalysis and electrochemistry.

Organic phase transmetallation approach for synthesis of hollow Ni-Au nanocomposites with tunable cavity size - Sardar, Debasmita; Ahmed, Md Azaharuddin; Bandyopadhyay, Sudipta; Ghosalya, Manoj Kumar; Bala, Tanushree (New Journal Of Chemistry, 2018)
Ni-Au nanocomposites in the form of hollow spheres with controlled cavity size have been successfully synthesized by the transmetallation reaction between hydrophobized Ni nanoparticles and hydrophobized Au precursors. This can be considered as a fairly unique synthesis strategy that does not require any additional external reductants. The synthesis is carried out in a nonpolar solvent and precise tuning of the cavity size has been achieved only by varying the ratio of the two reacting components. A detailed characterization has been performed via UV-vis spectroscopy, XPS, TEM, EDAX, and SEM. The mechanistic aspect is established from FTIR. SQUID-VSM confirmed the magnificent superparamagnetism of the nanocomposites.

Silicon oxidation by NAPPES: From dangling bonds to oxygen islands to 2D SiOx layer to the onset of bulk SiO2 formation - Ghosalya, Manoj Kumar; Jain, Ruchi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Valence band and core level photoelectron spectral measurements at near-ambient pressures (NAP; up to 0.5 mbar) were made in the presence of molecular oxygen to explore the various oxidation stages of silicon surfaces. Dangling bonds feature observed on clean Si-surfaces in the valence band at ultrahigh vacuum decreases dramatically due to oxygen adsorption between ambient temperature and up to 400 K at 0.1 mbar of O-2 pressure. The adsorption of oxygen on dangling bonds appears to be localized as islands; this reflects in the surface heterogeneous character and also responsible for the broadening in the oxygen gas phase vibrational features. This is further supported by an increase in the work function and can be correlated to the presence of Hofer (molecular) precursor. When the temperature was increased to 500 K, molecular precursor species dissociates to form Si-=-0 species. This is fully supported by the change in the Si work function as well as from the observation of oxidized Si species from Si 2p core level spectra. At >= 600 K, the Si-=-0 species dissociates to form a uniform 2D oxide layer on the silicon surface, which is characterized by the reappearance of sharp vibration features for gas-phase O-2 molecules. This layer is also quite stable up to 800 K and without any further oxidation in the bulk. On increasing the temperature to 850 K at 0.2 mbar oxygen pressure, bulk Si oxidation begins and the work function increases drastically by 1 eV. An angle-dependent Si 2p spectra recorded map out the presence of elemental Si to Si4+ from bulk to the surface, respectively. A simple model is proposed to show the various stage of silicon oxidation. A continuous change in the work function and electronic states observed due to gas-lattice (O-2-Si) interaction indicates the implications for surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, 2D layered materials.

Subtle interaction between Ag and O 2 : a near ambient pressure UV photoelectron spectroscopy (NAP-UPS) investigations - Ghosalya, Manoj Kumar (Journal of Chemical Sciences, 2018)
The Ag-O2 interaction, which is at the center-stage of Ag-catalyzed partial oxidation reactions, is studied with NAP-UPS up to 0.2 mbar O2 pressure between 295 and 550 K. Three temperature regimes were identified for distinct Ag-O2 interaction, which are (a) 295–390 K, where mainly dissociative chemisorption of O2 happens, (b) 390–450 K, where diffusion of O-atoms into the sub-surfaces of Ag is prominent, and (c) >450 K, where metastable oxide forms on polycrystalline Ag surfaces. The work function (WF) of Ag changed from 4.95 (≤390 K) to 5.30 eV (390–450 K), and then to 5.7 eV (≥450 K) at 0.1 mbar O2 pressure. Oxygen population in the sub-surfaces imparts crucial modifications to Ag at 390–450 K; it makes the surface to be electron-deficient that relates to the change in the WF of Ag and facilitates the formation of space charge layer on Ag surface. Oxygen adsorbed on such modified Ag-surfaces is electrophilic in nature, and this appears at a higher binding energy in core level XPS than the chemisorbed oxygen on metallic Ag. This is supported by angle-dependent NAP-XPS studies. The subsurface population of oxygen in Ag no longer persists at >410 K when the O2 supply is removed. A high ratio of antibonding/bonding O 2p bands suggests the unique silver-oxygen interaction under the measurement conditions.
Keywords: Electronic Structure; epoxidation; heterogeneous catalysis; Surface Science

Dexterous route for synthesis of hollow spherical ZnO and ZnO-Ag nanocomposite with superior photocatalytic ability - Maity, Jayeta; Bhattacharjee, Gourab; Satpati, Biswarup; Sardar, Debasmita; Ghosalya, Manoj Kumar; Bala, Tanushree (ChemistrySelect, 2019)
Hollow spherical ZnO and hollow ZnO-Ag nanocomposites with variable percentage of loading of Ag content were successfully fabricated through a novel, template free and easily reproducible route. Extensive characterizations were carried out using FTIR, XRD, XPS, BET, TEM and SEM. The hollow morphology of the particle and the composite encouraged a detailed photocatalysis study in comparison to solid commercial ZnO and the corresponding ZnO-Ag composite. The photocatalytic activity of the hollow particle and the composite was assessed monitoring the decolouration of methylene blue dye using UV-Vis absorption spectroscopic technique. An increased surface area for hollow morphology as compared to solid particles established a conspicuous boost in photocatalytic activity.
Keywords: excellent photocatalysis; synthesis; template free; ZnO hollow nanoparticles; ZnO-Ag nanocomposite

Oxidative disproportionation of MoS2/GO to MoS2/MoO3-x/RGO : integrated and plasmonic 2D-multifunctional nanocomposites for solar hydrogen generation from near-infrared and visible regions - Patra, Kshirodra Kumar; Ghosalya, Manoj Kumar; Bajpai, Himanshu; Raj, Sreeya; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2019)
Two dimensional (2D) semiconductor materials have been recently demonstrated to be effective plasmonic materials and alternatives to costly noble metals. However, tuning the plasmon resonance of 2D semiconductors and integrating with another material or semiconductor for various applications, such as solar light harvesting, remains a challenge. Herein, we designed a simple and attractive method, which facilitates the diffusion of oxygen from the graphene oxide (GO) layers of the MoS2/GO (MG) composite to oxidize the MoS2 layers significantly due to thermal treatment under inert atmosphere. This is the key step in the formation of MoS2/MoO3-x/RGO (MMR) (x = 0, 0.5, and 1, and all stoichiometries co-exist), due to disproportionation of MoS2/GO, with bulk heterojunctions among the components. The observed behavior is attributed to the oxidation of Mo4+ cations (of MoS2) to higher oxidation states in MMR (Mo(5+ )and Mo6+ of MoO3-x), which also alters the valence-band electronic structure and work function of the resulting composite. The 2D MoO3-x layers with a large amount of Mo5+ oxidation states enables facile charge carrier generation due to plasmonic effect, whereas MoS2 provides active sites for catalysis. The solar H-2 generation was demonstrated in the visible and near-infrared region by combining both the plasmonic and catalytic effects in one composite. These results demonstrate the important role of RGO to provide energy-level alignment, charge carrier diffusion, and help to generate plasmonic effect in the composite.

Gas-solid interactions with reactive and inert gas molecules by NAPUPS: can work function be a better descriptor of chemical reactivity? - Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ranjan, Ravi; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2020)
The gas-phase vibrational spectra of reactive (H(2)and O-2) and inert gases (N(2)and Ar) have been studied by near-ambient pressure (NAP) ultraviolet photoelectron spectroscopy (NAPUPS) up to 0.3 mbar pressure. The results obtained are divided into two parts and discussed. In the first part, the photoelectron spectra of monoatomic Ar and some homonuclear diatomic molecules, such as H-2, O-2, and N-2, have been recorded by NAPUPS and the effect of pressure on their energy position has been studied. It has been demonstrated that NAPUPS could be an essential tool to determine the intermolecular or interatomic interactions. In the second part, we have evaluated the influence of different solid surfaces on the binding energy (BE) position, the pattern of the vibrational features of diatomic N(2)molecules, and the first atomic levels (3p(3/2)and 3p(1/2)) of monoatomic Ar. It has been observed that with a change in the (electronic/chemical) nature of the surface, the BE of the above features also changes and reflects the change in the work function (phi) of the material. It is to be noted that Ar is an inert/noble gas and N(2)is the most stable molecule, and the above changes observed underscore that they can be employed as probe atoms/molecules to explore even the minor changes that occur on a solid surface due to a variety of reasons. Further, if the solid surface undergoes any chemical/electronic changes due to gas-solid interaction, such as oxidation/reduction, the phi of the surface changes again; this highlights the precise identification of the changes that occur under the reaction/measurement conditions. Therefore, the change in the BE of the gas-phase features can be used to determine even the minor changes in the phi of solid surfaces during the reaction or due to the reaction. The present findings have implications in probing the surface changes that occur in any surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, and materials that are predominantly controlled by surface contribution, such as layered (2D) materials, nanomaterials.